Evaluation of Prolidase Activity, Oxidative Stress, and Antioxidant Enzyme Levels in Testicular and Penile Tissues after Human Chorionic Gonadotropin Treatment in Rats by Predicting Infertility and Erectile Dysfunction - Pirincci, Necip; Yildirim, Serkan; Tas, Abuzer; Kuscu, Yagmur; Ozan, Tunc; Firdolas, Fatih; Karakeci, Ahmet (Karger, 2018)
Objectives: Prolidase plays a vital role in collagen turnover, matrix remodeling, and cell growth. We aimed to evaluate the association between treatment with chorionic gonadotropin and infertility and erectile dysfunction by investigating tissue prolidase activity, oxidative stress, and levels of antioxidant enzymes. Materials and Methods: The 16 male Wistar albino rats used in this study were randomly divided into 2 groups: rats treated with human chorionic gonadotropin (hCG) and control rats (n = 8 in each group). The rats in the hCG group were subcutaneously injected with 50 IU hCG daily for 15 days, while the rats in the control group were subcutaneously injected isotonic saline. All of the rats were sacrificed by a lethal overdose of sodium pentobarbital at the first month after hCG administration. Prolidase activity and levels of malonyl aldehyde, glutathione reductase, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) were estimated in the testicular and penile tissue. The testicles and penis were transversely dissected and placed in formalin. Results: Levels of prolidase and malonyl aldehyde in the testicular and penile tissues were significantly higher in the hCG group than in the control group (p < 0.001), while levels of glutathione reductase, SOD, GSH-Px, and CAT were significantly lower in the hCG group than in the control group (p < 0.001). Conclusions: In this study, we observed that treatment with hCG increased prolidase activity and oxidative stress and decreased the antioxidant capacity of penile and testicular tissues; therefore, this may affect fertility and erectile function. (C) 2018 The Author(s) Published by S. Karger AG, Basel
Keywords: Antioxidant; Human chorionic gonadotropin; Oxidative stress; Prolidase